Experimental study and computational analysis on pedestrians behaviour walking through angled-corridor - Rahman N.A.; Adenan S.H.M.; Alias N.A.; Kasehyani N.H.; Sukor N.S.A.; Halim H.; Katman H.Y. (American Institute of Physics Inc., 2023)
Thorough understanding of pedestrian flow is crucial due to immediate applications in building design, pedestrians and recreational facilities design, safety management and emergency evacuation assessment. This study was carried out due to lack of empirical data on pedestrian flow under the effect of corridor with corner. This article proposes a controlled experiment and presents several preliminary results on microscopic dynamics of pedestrians walk through an angled-corridor. Three different angled-corridors were considered: 60-, 90- and 135-corridor, with three different width of corridors: 1.50 m, 2.25 m and 3.00 m. Empirical results obtained are pedestrians trajectories, walking speed of pedestrian walking through corridors without and with a corner, walking speed of pedestrian walking through different width of angled-corridors, and lastly, pedestrian walking speed by gender. It is found that dimensional of corridor widths and angle of corridor influences the walking speed of pedestrians. The increasing in width of corridor has a positive impact to the walking velocity. In this study, two standards have been referred: Uniform Building by Law and Highway Capacity Manual 2010. The acquisition of empirical evidences on pedestrian walking behavior in architectural buildings or any built environment is important for the purpose of understanding the pedestrian flow and model validation. 2018 Author(s).